Black cumin seed oil preparation consumption potentially improves adaptive cellular immune response among healthy volunteers - Titiek Hidayati; Akrom Akrom; Arif Budi Setianto (International Journal of Public Health Science (IJPHS), 2022)
Oxidative stress and inflammatory reactions are the pathological mechanisms for most degenerative diseases. The black cumin seed oil (BCSO) contains compounds that can act as antioxidants and immunomodulators. Consuming BCSO is thought to improve antioxidant and immunomodulatory parameters in obese people. This study investigated the effect of BCSO consumption on antioxidant and immunomodulatory activity in healthy volunteers. We conducted a quasi-experimental study on 12 healthy volunteers in Yogyakarta, Indonesia. We asked the volunteers to consume BCSO for twenty days. We measured blood pressure, body mass index (BMI), malondialdehyde (MDA) level, Serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvate transaminase (SGPT) activity, CD4Th, and IFN-γ expression before and after consuming BCSO. We carried out the average difference test of the parameters before and after consumption of BCSO by dependent t-test. The results showed that 3x1 BCSO preparation for 20 days reduced MDA levels and increased CDTh and IFN-γ. Consuming BCSO for 20 days potentially improve the adaptive cellular immune response parameters.